Hazard of a neonicotinoid insecticide on the homing flight of the honeybee depends on climatic conditions and Varroa infestation. (June 2019) - Monchanin, Coline; Henry, Mickaël; Decourtye, Axel; Dalmon, Anne; Fortini, Dominique; Bœuf, Elodie; Dubuisson, Ludovic; Aupinel, Pierrick; Chevallereau, Colombe; Petit, Julie; Fourrier, Julie
Abstract: The paradigm for all toxicological bioassays in the risk assessment of pesticide registration reflects the principle that experimental conditions should be controlled to avoid any other factors that may affect the endpoint measures. As honeybee colonies can be frequently exposed to bio-aggressors in real conditions, often concomitantly with pesticides, co-exposure to pesticide/bio-aggressors is becoming a concern for regulatory authorities. We investigated the effects of the neonicotinoid insecticide thiamethoxam on the homing performances of foragers emerging from colonies differentiated by health status (infestation with Varroa destructor mites, microsporidian parasite Nosema spp. and Deformed Wing Virus). We designed a homing test that has been recently identified to fill a regulatory gap in the field evaluations of sublethal doses of pesticides before their registration. We also assessed the effect of temperature as an environmental factor. Our results showed that the Varroa mite exacerbates homing failure (HF) caused by the insecticide, whereas high temperatures reduce insecticide-induced HF. Through an analytical Effective Dose (ED) approach, predictive modeling results showed that, for instance, ED level of an uninfested colony, can be divided by 3.3 when the colony is infested by 5 Varroa mites per 100 bees and at a temperature of 24 °C. Our results suggest that the health status of honeybee colonies and climatic context should be targeted for a thorough risk assessment. Graphical abstract: Image 1 Highlights: Temperature and colony health modulate insecticide-induced homing failure in honeybee. Varroa mites exacerbate homing failure caused by the insecticide thiamethoxam. Low temperatures aggravate insecticide-induced homing failure. Pesticide risk assessment should include temperature and Varroa mites as covariates.